Health-related quality of life of university students from Wrocław - Puciato, Daniel (Jakość życia związana ze zdrowiem studentów z Wrocławia, 2019)
The aim of the study is to assess health-related quality of life among students from Wrocław, Poland. The research was carried out in 2014 and 2015. The study sample consisted of 637 people (441 women, 196 men). The main research method used in the study was a diagnostic survey poll. The research tool was the World Health Organization Quality of Life (WHOQOL BRIEF) questionnaire. The results of the study showed that the majority of the surveyed students assessed their health-related quality of life as average. Mean scores for overall health-related quality of life, perceived health condition, and quality of life in the physical, psychological, social and environmental domains were higher among men than women. Among all the respondents, significant differences in quality of life ratings were also noted in individual domains. The respondents rated their health-related quality of life in the social domain as the highest, and in the physical domain as the lowest
Biblioteka Regionalisty, 2019, Nr 19, s. 180-190
Keywords: Dolny Śląsk